Low-Intensity Focused Ultrasound Stimulation on Fingertip Can Evoke Fine Tactile Sensations and Different Local Hemodynamic Responses - Liuni Qin; Mingyang Dou; Lili Niu; Laixin Huang; Fei Li; Shichun Bao; Xinping Deng; Guanglin Li; Yanjuan Geng (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Low-intensity focused ultrasound stimulation (LIFUS) has been proved effective in eliciting vibrotactile in addition to warm, cold and nociceptive pain when applied to human peripheral endings. However, if it can evoke fine tactile sensations has been rarely investigated by far despite the importance of fine tactile feedback in motor control. To explore this issue, 14 healthy volunteers were recruited in this study. A psychophysical experiment was firstly conducted to determine the appropriate range of pulse repetition frequency (PRF) and acoustic intensity (AI). Then, participants were asked to perceive and discriminate different tactile stimulations under LIFUS, so as to evaluate if multiple fine tactile sensations could be reliably elicited by modulating the PRF and AI. For objective assessment, the local blood perfusion volume (BPV) response beneath stimulated fingertip was recorded and characterized. Our results showed that four types of tactile sensations, including tapping, vibrating, electrical, and pressure could be reliably elicited by modulating the PRF and AI within a specific range, and there was a significant impact of PRF and AI on both participants’ tactile discrimination and amplitude features of BPV response. This study would facilitate the application of LIFUS to some human-machine interaction scenarios, and shed valuable insights on the physiological mechanisms of peripherally applied ultrasound stimulation.